Family Firm Heterogeneity and Governance: A Configuration Approach. (April 2014) - Nordqvist, Mattias; Sharma, Pramodita; Chirico, Francesco; Carsrud, Alan; Cucculelli, Marco
<x xml:space="preserve">Abstract</x> Family involvement in ownership and management of business varies significantly within family firms. Although the literature recognizes the diversity in family firms, it remains unclear what governance mechanisms are most appropriate to achieve prioritized performance goals of different types of family firms. By combining two established categorizations of family involvement in firm ownership and management, nine types of family firms are identified. Drawing on the configuration approach, we theorize the governance mechanisms likely to most efficiently address the incentive systems, authority relations, and norms of legitimization in each of these types of family firms.